2017
DOI: 10.1080/10408398.2017.1379947
|View full text |Cite
|
Sign up to set email alerts
|

Pistachio nut allergy: An updated overview

Abstract: Pistachio nut (Pistacia vera) is highly appreciated for its organoleptic characteristics and potential health benefits. However, this tree nut is also responsible for triggering moderate to severe IgE-mediated reactions in allergic individuals. Currently, pistachio nut allergy has gained some special attention, mainly due to its intrinsic relation with cashew nut allergy. Like for other nuts, the prevalence of pistachio nut allergy seems to be increasing at a global scale. Until now, there are five allergenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 92 publications
1
30
1
3
Order By: Relevance
“…It should also be noted that, although there are differences between individuals, they all recognize 2S albumins, both pistachio (Pis v 1) and cashew (Ana o 3), except P10. Previous studies have already described the high reactivity of the albumin of these two nuts; Pis v 1 is a major allergen that has been shown to be detected by more than 50% of sera from pistachio-allergic patients [5]. Regarding Ana o 3, it has been determined that it is detected by 93% of children allergic to cashew nuts, becoming a clinical indicator of cashew allergy, being even more specific than the whole extract [33].…”
Section: Immunodetection With Ige From Human Seramentioning
confidence: 97%
“…It should also be noted that, although there are differences between individuals, they all recognize 2S albumins, both pistachio (Pis v 1) and cashew (Ana o 3), except P10. Previous studies have already described the high reactivity of the albumin of these two nuts; Pis v 1 is a major allergen that has been shown to be detected by more than 50% of sera from pistachio-allergic patients [5]. Regarding Ana o 3, it has been determined that it is detected by 93% of children allergic to cashew nuts, becoming a clinical indicator of cashew allergy, being even more specific than the whole extract [33].…”
Section: Immunodetection With Ige From Human Seramentioning
confidence: 97%
“…It should also be noted that, although there are differences between individuals, they all recognize 2S albumins, both pistachio (Pis v 1) and cashew (Ana o 3), except P10. Previous studies have already described the high reactivity of the albumin of these two nuts, Pis v 1 is a major allergen that has been shown to be detected by more than 50% of sera from pistachio-allergic patients [6]. Regarding Ana o 3, it has been determined that it is detected by 93% of children allergic to cashew nuts, becoming a clinical indicator of cashew allergy, being even more specific than the whole extract [39].…”
Section: Immunodetection With Ige From Human Seramentioning
confidence: 96%
“…In lentil and chickpea the band intensity decreased respect to the control, although changes were hardly observed between the different treatments, this fact leads to deduce that the conditions of the DIC8 treatment are more favorable for the decrease in the number and intensity of protein bands. However, even under these conditions, protein bands are still observed, especially those with low molecular weight (2S albumins, Pis v 1 and Ana o 3), it has been shown that this type of protein is able to maintain its integrity in drastic processing and digestion conditions [6,35], which confirms its high stability and difficulty of elimination.…”
Section: 3-electrophoretic Analysismentioning
confidence: 98%
“…Several major allergens have been identified in cashew ‐Ana o 1 (7S vicilin), Ana o 2 (11S globulin), Ana o 3 (2S albumin), and in pistachio ‐Pis v 1 (2S albumin), Pis v 2 and 5 (11S globulin), Pis v 3 (7S globulin) and Pis v 4 . Except Pis v 4, a manganese superoxide dismutase, all others are seed storage proteins.…”
Section: Patients’ Clinical Featuresmentioning
confidence: 99%